2014
DOI: 10.2139/ssrn.2409010
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Unemployment and Wage Inertia

Abstract: We introduce wage setting via e¢ ciency wages in the neoclassical one-sector growth model to study the growth e¤ects of wage inertia. We compare the dynamic equilibrium of an economy with wage inertia with the equilibrium of an economy without it. We show that wage inertia a¤ects the long run employment rate and that the transitional dynamics of the main economic variables will be di¤erent because wages are a state variable when wage inertia is introduced. In particular, we show that the model with wage inerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Commercial banks hold vault cash, and a tax is levied on vault cash holdings. In addition, I provide a microfoundation for nominal wage stickiness by modifying the fair wage setting of Raurich and Sorolla (2014).…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Commercial banks hold vault cash, and a tax is levied on vault cash holdings. In addition, I provide a microfoundation for nominal wage stickiness by modifying the fair wage setting of Raurich and Sorolla (2014).…”
Section: Modelmentioning
confidence: 99%
“…(3) −n t f (e t ) denotes the disutility of effort, where n t is the amount of employed labor, e t is effort per unit of employed labor, and −f (e t ) is the disutility of effort per unit of employed labor. Following Raurich and Sorolla (2014), I assume a quadratic disutility function:…”
Section: Householdmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper [17] has found a negative relation between long-run economic growth and unemployment. In the article [18] authors introduce wage inertia in the neoclassical one sector growth model. In the paper [19] is shown that a standard flexible price model with labour market frictions that allows hiring costs to depend on technology shocks may also lead to the same negative impact on labour inputs.…”
Section: Introductionmentioning
confidence: 99%